Correction: Baláž et al. Mechanochemistry as an Alternative Method of Green Synthesis of Silver Nanoparticles with Antibacterial Activity: A Comparative Study. Nanomaterials 2021, 11, 1139 - Matej Baláž; Zdenka Bedlovičová; Nina Daneu; Patrik Siksa; Libor Sokoli; Ľudmila Tkáčiková; Aneta Salayová; Róbert Džunda; Mária Kováčová; Radovan Bureš; Zdenka Lukáčová Bujňáková (Nanomaterials)
In the original publication [...]